Genetic analysis of candidate loci in non-syndromic cleft lip families from Antioquia-Colombia and Ohio (2004)
ABSTRACT: Non-syndromic cleft lip with or withoutcleft palate (CL/P) is a genetically complexbirth defect, with a prevalence from 1/500 to1/1,000 live births. Evidence from linkageand linkage disequilibrium studies is con-tradictory suggesting that heterogeneity be-tween study populations may exist. A recentreport of a genome widescan in 92 sib pairsfrom the United Kingdom revealed sugges-tive linkage to 10 loci [Prescott et al., 2000].The purpose of this study is to replicate thoseresults and evaluate additional candidategenes in 49 Colombian and 13 Ohio families.Genotypes were obtained for STRPs at 1p36,2p13 (TGFA), 4p16 (MSX1), 6p23-25, 6q25-27,8q23-24, 11p12-q13, 12q13, 14q24 (TGFB3),16q22-24, 17q12-21 (RARA), and Xcen-q21.Linkage was performed using parametric(dominant and recessive models) and non-parametric (GenehunterNPL and SimIBD)analyses. In addition, heterogeneity wasanalyzed using GenehunterHLOD, andassociation determined by the TDT. TheColombianfamiliesshowedsignificantSimIBD results for 11p12-q13 (P¼0.034),12q13 (P¼0.015), 16q22-24 (0.01), and 17q12-21 (0.009), while the Ohio families showedsignificant SimIBD results for 1p36 (P¼0.02),TGFA (P¼0.005), 6p23 (P¼0.004), 11p12-q13(P¼0.048) and significant NPL results forTGFA (NPL¼3.01,P¼0.009), 4p16 (MNPL¼2.07,P¼0.03) and 12q13 (SNPL¼3.55,P¼0.007). Significant association results wereobtained only for the Colombian familiesin the regions 1p36 (P¼0.046), 6p23-25(P¼0.020), and 12q13 (P¼0.046). In additionseveral families yielded LOD scores rangingfrom 1.09 to 1.73, for loci at 4p16, 6p23-25,16q22-24, and 17q13. These results confirmprevious reports for these loci. However, thedifferences between the two populationssuggest that population specific locus het-erogeneity exists.